Altered Cortical Gamma-Amino Butyric Acid in Female Veterans With Suicidal Behavior: Sex Differences and Clinical Correlates. (March 2018) - Prescot, Andrew; Sheth, Chandni; Legarreta, Margaret; Renshaw, Perry F.; McGlade, Erin; Yurgelun-Todd, Deborah
Background: Suicide is a public health concern in the civilian and veteran populations. Stressful life events are precipitating factors for suicide. The neurochemical underpinnings of the association between stress/trauma and suicide risk are unclear, especially with regard to sex differences. We hypothesized that gamma-amino butyric acid (GABA), the major inhibitory neurotransmitter, may be a neurochemical candidate that is critical in the association between stress and suicide risk in veterans. Methods: Proton magnetic resonance spectroscopy at 3.0 Tesla was used to measure in vivo neurochemistry in the anterior cingulate cortex (predominantly the dorsal anterior cingulate cortex) of 81 veterans (16 females), including 57 (11 females) who endorsed past suicidal ideation and/or suicide attempt and 24 (5 females) with no history of suicidal ideation and/or suicide attempt. Suicidal behavior (SB) was defined as the presence of suicidal ideation and/or suicide attempt. Results: We observed no significant differences in GABA/creatine + phosphocreatine (Cr + PCr) between veterans with SB (SB+) and without SB (SB−). However, the female SB+ group showed significantly reduced GABA/Cr + PCr versus the female SB− group. We observed a trend-level significant negative correlation between GABA/Cr + PCr and the Defensive Avoidance subscale on the Trauma Symptom Inventory in the SB+ group. In contrast, the SB− group exhibited a positive relationship between the two variables. Furthermore, we found significant negative correlations between GABA/Cr + PCr and Hamilton Rating Scale for Depression scores as well as between GABA/Cr + PCr and several subscales of the Trauma Symptom Inventory in female veterans. Conclusions: This study suggests that reduced GABA/Cr + PCr ratio in the anterior cingulate cortex, which may be related to altered inhibitory capacity, may underlie suicide risk in female veterans. Further, the negative association between GABA/Cr + PCr and stress symptomatology and depression scores suggests that magnetic resonance spectroscopy studies may shed light on intermediate phenotypes of SB.